Development of Literacraft-Based Social Studies Modules to Increase Environmental Responsibility Behavior of Grade V Elementary School Students - Ravi’ah, Siti; Hidayat, Otib Satibi; Lestari, Ika (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
The problems that occur in grade V elementary school students are related to their knowledge and understanding of the environment and their awareness of the importance of preserving the environment. This research is only focused on grade V elementary school students, and discusses the development of LiteraCraft-based modules as a solution in improving students' knowledge and understanding of the environment and increasing students' responsibility of environmental behavior. This research uses the R&D method with the ADDIE model which includes analysis, design, development, implementation, and evaluation. Conducted at SDN 09 Sungai Nanam, this study collected data from interviews, tests, and questionnaires during the first semester of the 2023/2024 school year. The research results showed positive results. The expert assessment stated that the media, language, and material of the module were very good. The correctness of the material, feasibility of presentation, and technical quality are the highest aspects. Small group trials with 5 students showed the module was good and appropriate, with efficiency as the highest aspect. Field trials with 20 fifth grade students showed excellent results, with participation in environmental conservation as the highest aspect. The attitude test with 28 students showed the module was very appropriate, with respect for the earth as the highest aspect. T-test showed a significant difference in environmental responsibility behavior before and after using the module. The N-Gain test showed a 61.3% increase in students' environmental responsibility scores